THE LEVEL OF MOTIVATION AND SELF-REGULATION AS DETERMINANTS OF THE QUALITY OF PUPILS FUNCTIONING IN THE SCHOOL ENVIRONMENT - Iłendo-Milewska, Agnieszka (PEOPLE: International Journal of Social Sciences, 2017)
Background: The content of the article focuses on the issue of self-regulation of middle school students, showing its significance in adolescent, in the light of the Theory of Self-Regulation (Deci), the concept of Baumeister’s self-regulation and the Helping Relationship Theory by Lawrence M. Brammer. Various research has been conducted among middle school students, in order to establish the relationship between the level of selected areas of self-regulation and the quality of functioning in the school environment in the perception of those students. Theoretical viewpoint is the basis for the empirical part of the article. Aims: It was assumed that there is a correlation between the level of motivation and the level of self-regulation and the quality of student's functioning in the school environment.Method: To measure the aspects of self-regulation, two questionnaire were used: the first one: Learning Regulation Questionnaire (Deci & Williams, 1996) and the School Motivation Questionnaire (Sterczyński, 2010). The F/D-U survey (Gaś, 2004) was used to measure the aspects of the basic conditions in the process of supporting a child in his or her way of achieving maturity. Results and conclusion: The research analysis and conclusions constitute the practical implication in the field of the quality of pupils' functioning in the school environment. They constitute the practical implication in the field of the quality of functioning pupils in the school environment. The results can help to create effective preventive and educational impact in the school environment.